Interlaboratory assessment of candidate reference materials for lentiviral vector copy number and integration site measurements - Hua-Jun He; Zhiyong He; Steven P. Lund; Laure Turner; Yongjun Fan; Yu Qiu; David C. Corney; Boro Dropulic; Rimas Orentas; Oxana Slessareva; Priscilla Welch; Katie Dungca; et al. (Molecular Therapy: Methods & Clinical Development)
While lentiviral vectors have played a critical role in the emergence of gene-modified cell therapies, safety concerns remain regarding potential insertional mutagenesis. Regulatory authorities strongly recommend risk assessment and management of vector copy numbers (VCNs), integration profiles, and integration sites in the lentivirus-based cell and gene therapy products. However, accurately measuring these parameters remains a significant challenge due to the lack of standardized methodologies and VCN reference materials (RMs). Toward this challenge, we conducted an interlaboratory study on NIST candidate RMs for VCN measurements. The candidate RMs comprise five human genomic DNA samples or fixed cells from clonal Jurkat cell lines with defined VCNs ranging from 0 to 4. All 12 study participants were able to identify the VCN in the five blinded samples using quantitative PCR (qPCR), digital PCR (dPCR), or next generation sequencing (NGS) assays. Consensus value of VCN and integration sites in these candidate RMs were achieved. The fixed clonal VCN cells were also used to evaluate an emerging imaging-based technology called molecular combing. This interlaboratory assessment demonstrated the utility, commutability, and suitability of the NIST VCN candidate RMs for quality assurance and improved confidence in VCN, integration profile, and integration site measurements.